1991
DOI: 10.1085/jgp.98.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state gating of batrachotoxin-modified sodium channels. Variability and electrolyte-dependent modulation.

Abstract: A B S T RA CTThe steady-state gating of individual batrachotoxin-modified sodium channels in neutral phospholipid bilayers exhibits spontaneous, reversible changes in channel activation, such that the midpoint potential (V~) for the gating curves may change, by 30 mV or more, with or without a change in the apparent gating valence (za). Consequently, estimates for V a and, in particular, z a from ensembleaveraged gating curves differ from the average values for V, and z~ from singlechannel gating curves. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 57 publications
(109 reference statements)
1
7
0
Order By: Relevance
“…The drug's low-and high-Kd periods were long-lived (seconds to minutes), and such long lifetimes resemble those displayed by the various channel activation-gating modes (Chabala et al, 1991). In fact, all the studied channels showed activation-gating modes (not shown).…”
Section: Changes In the Low-k D Values And The Lack Of Local Anesthetmentioning
confidence: 81%
See 1 more Smart Citation
“…The drug's low-and high-Kd periods were long-lived (seconds to minutes), and such long lifetimes resemble those displayed by the various channel activation-gating modes (Chabala et al, 1991). In fact, all the studied channels showed activation-gating modes (not shown).…”
Section: Changes In the Low-k D Values And The Lack Of Local Anesthetmentioning
confidence: 81%
“…Based on this resemblance, one could postulate the presence of various open channel states with different equilibrium rates with the closed (resting) state as the underlying mechanism for the activation-gating modes. Brain- (Chabala et al, 1991) and muscle-derived (French et al, 1986;Moczydlowski et al, 1984;Recio-Pinto et al, 1987) sodium channels displayed activation-gating modes, whereas only brain channels displayed various anesthetics' Kd periods. This suggests that, in musclederived sodium channels, the various open channel states have different equilibrium with the resting state but the same affinity for local anesthetics, whereas in brain channels these open states have different local anesthetic affinity and different equilibrium with the resting state.…”
Section: Changes In the Low-k D Values And The Lack Of Local Anesthetmentioning
confidence: 99%
“…Here, it is demonstrated that both intracellular and extracellular divalent cations, more specifically Ba2+, are still capable of altering the gating of Na+ channels in high ionic strength solutions. These results demonstrate that, in addition to their screening effects on diffuse surface charges on the Na+ channel glycoprotein and membrane (Cukierman et al, 1988;Cukierman, 1991a,b;Chabala et al, 1991;Correa et al, 1991), divalent cations exert a very specific modulatory effect on the gating of Na+ channels.…”
Section: Introductionmentioning
confidence: 77%
“…By reconstituting single Na+ channels in neutral planar lipid membranes, it has been clearly demonstrated that membrane surface charges are not really necessary for divalent cations to modify the gating of Na+ channels (Green et al, 1987;Cukierman et al, 1988;Krueger, 1990, 1991;Chabala et al, 1991;Cukierman, 1991a,b;Correa et al, 1991Correa et al, , 1992Moczydlowsky and Schild, 1993). The presence of negative surface charges located on both sides of the Na+ channel glycoprotein is a sufficient condition for external (or internal) divalent cations to shift the gating curve of Na+ channels to more positive (or negative) membrane voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The observed heterogeneity in cGMP binding of 1BUs may also result from an intrinsic heterogeneity of the presumed homomultimers, because n is usually found to be < 1 for channels expressed in oocytes. The mechanistic basis for such heterogeneity is obscure, but a similar heterogeneity (over time) has been observed in voltaged e p e n d e n t sodium channels in oocytes (Zhou et al 1991) and in planar bilayers (Chabala et al, 1991). In the latter system, at least, one can exclude the possibility that covalent modification of the channel protein is involved.…”
mentioning
confidence: 90%